Critical citizenship and social studies for the present - Plá Pérez, Sebastián (2020)
In the following pages, the conference by Dr. Sebastián Plá Perez, from UNAM (México), given as part of the launch of the Central American Network of Research and Teaching in Social Studies and Critical Citizenship, is reproduced. Social studies and critical citizenship are problematized in the writing as fields that produce antagonisms in contemporary societies, due to the political character of their teaching.